2002
DOI: 10.1055/s-0037-1613166
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Comparative Evaluation of a Novel PAI-1 Inhibitor

Abstract: SummaryPlasminogen activator inhibitor-1 (PAI-1), the primary physiological inhibitor of both tissue-type plasminogen activator and urokinasetype plasminogen activator in plasma, is a well established risk factor in thrombotic diseases. Reduction of active PAI-1 levels may lead to a decreased tendency of thrombosis. Compounds that can suppress pharmacologically active PAI-1 levels are therefore considered as putative drugs.In the present study, we describe the PAI-1 neutralizing properties and mechanism of a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 47 publications
(48 reference statements)
1
25
0
Order By: Relevance
“…Consistent with studies showing that PAZ-417 directly inhibits PAI-1 in the brain, immunohistochemistry studies showed that PAI-1 protein levels are reduced in the hippocampus of transgenic AD mice after drug treatment (data not shown). This observation is consistent with studies demonstrating that the half-life of PAI-1 is significantly reduced when bound by smallmolecule inhibitors (32).…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with studies showing that PAZ-417 directly inhibits PAI-1 in the brain, immunohistochemistry studies showed that PAI-1 protein levels are reduced in the hippocampus of transgenic AD mice after drug treatment (data not shown). This observation is consistent with studies demonstrating that the half-life of PAI-1 is significantly reduced when bound by smallmolecule inhibitors (32).…”
Section: Discussionsupporting
confidence: 92%
“…Synthetic Compounds-The IC 50 value obtained with 7 nM TA was ϳ1000-fold lower than our previously reported IC 50 value for the PAI-1 inactivator, PAI-039 (32), and is markedly lower than any previously reported small-molecule PAI-1 inactivating compound (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). Likewise the IC 50 values obtained with EGCG and EGCDG were also significantly better than PAI-039 and most other PAI-1 inactivators, suggesting that galloyl-containing compounds may represent a potent new family of PAI-1 inactivating compounds.…”
Section: Resultsmentioning
confidence: 55%
“…The flexible structure of PAI-1, the lack of a rigid active site, and its multiple functions all contribute to the difficulties in identifying and designing small-molecule PAI-1 inactivators. Despite these obstacles, several small-molecule PAI-1 inhibitors have been described (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36); however, each has significant limitations that have reduced their potential for further drug development.…”
mentioning
confidence: 99%
“…Small-molecule synthetic antagonists of PAI-1 have been described previously (Charlton et al, 1996;Friederich et al, 1997;Neve et al, 1999;Gils et al, 2002;Einholm et al, 2003;Elokdah et al, 2004;Liang et al, 2005;Gorlatova et al, 2007). The metastable conformation of PAI-1 along with the intricacies of the pathway by which PAI-1 inhibits tPA affords numerous potential opportunities whereby a PAI-1 inhibitor could block PAI-1 activity.…”
mentioning
confidence: 99%